Esophageal Submucosal Hematoma Possibly Caused by Gastric Tube Insertion Under General Anesthesia. Issue 8 (15th October 2016) - Fujimoto, Yuri; Shirozu, Kazuhiro; Shirozu, Noritoshi; Akiyoshi, Kozaburo; Nishimura, Ataru; Kawasaki, Sho; Motoyama, Yoshimasa; Kandabashi, Tadashi; Iihara, Koji; Hoka, Sumio
Abstract : We present a case of an esophageal submucosal hematoma that developed after endovascular treatment for coil embolization for an unruptured cerebral aneurysm. The patient had received antiplatelet therapy before surgery and anticoagulation therapy during surgery. The orogastric tube was removed at case end with sustained negative pressure. After surgery, the patient reported chest and back pain and was diagnosed with an esophageal submucosal hematoma. The hematoma might have been related to the gastric tube insertion or removal. Providers should keep in mind the possibility of this complication when a patient who was given antithrombotic therapy reports chest or back pain after surgery.